(untitled) (Journal of Parents and Teachers, 2014)
Parents ignored the content of their children’s video games ... until the alarms went off. Too much violence in them. However, video games are now judged and seen as catastrophic. It has been proven that there is no relationship between the violence of a video game and that the person who plays it is violent. What would be interesting, without a doubt, would be to investigate about video games in our classrooms.